A Patient with Clavicle Fracture and Recurrent Scapular Winging with Spontaneous Resolutions - Kendra E. Keenan; John G. Skedros (Case Reports in Orthopedics)
Injury to the long thoracic nerve with resulting serratus anterior palsy is a typical cause of medial scapular winging. We report a case of a 70-year-old female with scapular winging in the setting of a mildly comminuted midshaft clavicle fracture. The winging persisted for three months after the fracture, which became a nonunion. The winging spontaneously resolved prior to open reduction and internal fixation of the nonunion. The winging recurred after this surgery. The recurrence was attributed to transient irritation and/or inflammatory neuropathy of the brachial plexus caused by the surgical manipulation. This second episode of winging again spontaneously resolved. There are few reported cases of scapular winging in the setting of a clavicle fracture and only one case of recurrent scapular winging. In that case, which was in the setting of an acromioclavicular joint separation, the second episode of winging required long-term use of a brace. By contrast, our patient did not require bracing because the recurrent winging spontaneously resolved, making this a novel case. This case is important because it illustrates that recurrent scapular winging can occur, and spontaneously resolve, in the setting of a mid-shaft clavicle fracture after subsequent reconstruction of a fracture nonunion.